The Legitimising Project: The Coronation Rite and the Written Word - Orlowska, Izabela (Aethiopica, 2013)
The article and its argument are based on a hitherto unexplored Ethiopian chronicle, which offers a uniquely detailed description of a series of enthronement rites. The article explores and deciphers symbolism displayed in these acts, which was drawn from the past and remodelled to form ideological underpinning for the monarchy of Yoḥannǝs IV (1872–89) and to legitimise his imperial project. The article argues that despite the fact that the record of these events is likely to have been ‘adjusted’ by Ethiopian chroniclers, their writings still points to what they thought should happen during a ritual in order for it to be effective. Consequently, the authors of the chronicle revealed to us the role of ritual in the legitimising project of late 19th-century Ethiopia.